Caracterização biométrica e germinação de mabolo (Diospyros blancoi Willd) - Vilcatoma Medina, Carlos [UNESP] (2014)
Diospyros blancoi Willd, popularly known as Mabolo, is an exotic fruit native to the Philippines. Growth is enhanced by tropical climatic conditions, adapting in almost all Brazil. It is a still little studied specie, although their fruits present important nutritional and medicinal properties. This research was conducted in order to better understand the specie and have information about the propagation to obtain seedlings through biometric characterization of the fruits, leaves and seeds, and germination at different temperatures, storage periods and substrates.To this end, were used three accesses of Mabolo belonging to Active Germplasm Bank of UNESP – Univ Estadual Paulista, Jaboticabal city, São Paulo state, Brazil. The biometric evaluations of the leaves consisted of measuring the width, length and leaf area, and petiole length. In fruits and seeds were evaluated the width, length and mass, plus the percentage of pulp. For the germination test were used the temperatures of 20, 25, 30, 35 and 20-30°C in B.O.D.; beyond germination on vermiculite, pine bark, coconut fiber and soil misture + sand + corral manure (in proportion of 3: 1: 1). Biometric classification based on frequency ranges of Mabolo fruit revealed that access A1 shows a bigger quantity of fruits with average percentage of fruit pulp and bark with lighter. A comparison of accesses based only on mean showed that the A3 access had higher mean weight, length and width of fruit, plus the mass of pulp. The leaf biometrics in access A3 showed only the higher mean leaf width and petiole length. Both biometric classification in frequency ranges, such as the use of means showed only minor differences between accesses of Mabolo with relation to leaf biometrics, not evidencing changes in leaf morphology of plants of the three accesses. For germination, the access A3 presents the best rates; the temperature recommended for the mabolo should be 30°C and seeding should be ...